How is healthy eating index-2015 related to risk factors for cardiovascular disease in patients with type 2 diabetes - Zeinalabedini, Mobina; Nasli-Esfahani, Ensieh; Esmaillzadeh, Ahmad; Azadbakht, Leila (Frontiers in Nutrition, 2023)
Background Cardiovascular disease (CVD) is the primary cause of mortality and disability among diabetes. The aim of this study is to evaluate how healthy eating index-2015 related to risk factors for cardiovascular disease in patients with type 2 diabetes. Methods This cross-sectional study was conducted on 490 patients with type 2 diabetes in Tehran, Iran. The healthy eating index-2015 (HEI-2015) used as a diet quality indicator. Dietary intake was assessed by a valid and reliable semi-quantitative food frequency questionnaire (FFQ). Four indicators of CVD risk factor [Castelli risk index-1 and 2 (CRI-II), atherogenic index of plasma (AIP), cholesterol index (CI), and lipid accumulation of plasma (LAP)] were calculated. The anthropometric indices [a body shape index (ABSI), abdominal volume index (AVI), and body roundness index (BRI)] were computed. Results After adjusting for potential confounders, it is evident that participants in the highest tertile of HEI had a lower odds ratio of BRI (OR: 0.52; 95% CI: 0.29–0.95; p-trend = 0.03) and AIP (OR:0.56; 95% CI: 0.34–0.94; p-trend = 0.02). Also, HEI and CRI had a marginally significant negative relation (OR: 0.61; 95% CI: 0.38–1; p-trend = 0.05) in crude model, after adjusting the signification disappeared. Conclusion In conclusion, our finding shows that more adherence to HEI reduces about 50% of the odds of AIP, BRI among diabetic patients. Further, large-scale cohort studies in Iran need to confirm these findings, including diabetic patients of various racial, ethnic backgrounds, body composition and different components of HEI.